AB0037 EXPRESSION OF NEGATIVE CHECKPOINT MOLECULES BTLA AND HVEM IS DYSREGULATED IN AUTOIMMUNE DISEASES. (2nd June 2020) - Nagpal, S.; Cole, S.; Floudas, A.; Wechalekar, M.; Song, Q.; Gordon, T.; Caricchio, R.; Veale, D.; Fearon, U.; Rao, N.; Hao, L. Y.
Abstract : Background: Immune checkpoint blockade with agents targeting CTLA4 and PD-1/PD-L1 alone or in combination has demonstrated exceptional efficacy in multiple cancer types by "unleashing" the cytotoxic action of quiescent, tumor-infiltrating T cells. However, the therapeutic action of these immunotherapies goes hand in hand with the loss of immune tolerance and appearance of immune-related adverse events such as colitis, arthralgia and inflammatory arthritis in responsive patients. Therefore, immune checkpoint molecules have been proposed as targets for the treatment of autoimmune diseases. Objectives: Herein, we interrogate the potential of BTLA/HVEM axis as a target for restoring immune homeostasis in rheumatoid arthritis (RA), Systemic Lupus Erythematosus (SLE) and Sjogren's Syndrome (SjS) by examining their expression patterns in autoimmune disease tissues. Methods: Message and protein expression of BTLA and HVEM were examined in RA and SLE synovial tissues, SLE cutaneous lesions, SjS salivary glands and peripheral blood samples of autoimmune disease by RNA sequencing and flow cytometry. Results: Tissue dysregulation of the BTLA-HVEM axis was observed: Increased BTLA RNA level in RA synovium, SLE-affected skin, and SjS salivary gland samples, whereas HVEM level was affected only in the RA synovium when compared to unaffected tissues. Detailed immunophenotyping of B, T, and myeloid cell populations in RA, SLE, SjS and healthy control PBMCs revealed differential modulation of the BTLA+ or HVEM+ immune cell subsets in a disease-context dependent manner. SjS patients showed an overall decrease in memory B cells and most of the BTLA+ B cell subsets while a decrease in HVEM+ B cells was observed only in SLE PBMC samples and not RA and SLE samples. Immunophenotyping with a T cell panel exhibited decreased BTLA and HVEM expression on T cell subsets in SjS and SLE but not in RA patients. In addition, protein levels of HVEM were differentially decreased in SLE myeloid cell subsets. Finally, we demonstrate tissue-specific surface expression patterns of BTLA in RA and SLE samples: higher surface BTLA levels on RA and SLE PBMC B cells than matched tissue-derived B cells. Conclusion: Our results demonstrate a dysregulation of the BTLA/HVEM axis in either lesional tissue or peripheral blood in an autoimmune disease context-dependent manner. These results also indicate the potential of targeting BTLA-HVEM axis for the treatment of multiple autoimmune diseases. Disclosure of Interests: Sunil Nagpal Shareholder of: Janssen Pharmaceuticals, Employee of: Janssen Pharmaceuticals, Suzanne Cole Shareholder of: Janssen Research & Development employee, Employee of: Janssen Research & Development employee, Achilleas Floudas: None declared, Mihir Wechalekar Grant/research support from: Grant from Janssen Research & Development, Qingxuan Song Shareholder of: Employee of Janssen Research, Employee of: Employee of Janssen Research, Tom Gordon: None declared, Roberto Caricchio Grant/research support from: Financial grant from Janssen Research & Development, Douglas Veale: None declared, Ursula Fearon: None declared, Navin Rao Shareholder of: Janssen Pharmaceuticals, Employee of: Janssen Pharmaceuticals, Ling-Yang Hao Shareholder of: Employee of Janssen Research, Employee of: Employee of Janssen Research